An oral NaV1.8 blocker improves motor function in mice completely deficient of myelin protein P0. (6th October 2016) - Rosberg, Mette R.; Alvarez, Susana; Krarup, Christian; Moldovan, Mihai
Highlights: P0 -/- mice showed from birth a severe dysmyelinating neuropathy. The motor behavioral performance declined during the first 4 months of life. Motor excitability measures showed a progressive resting membrane depolarization. Motor performance and excitability could be improved by an oral NaV 1.8 blocker. Abstract: Mice deficient of myelin protein P0 are established models of demyelinating Charcot-Marie-Tooth (CMT) disease. Dysmyelination in these mice is associated with an ectopic expression of the sensory neuron specific sodium channel isoform NaV 1.8 on motor axons. We reported that in P0 +/−, a model of CMT1B, the membrane dysfunction could be acutely improved by a novel oral NaV 1.8 blocker referred to as Compound 31 (C31, Bioorg. Med. Chem. Lett. 2010, 20, 6812; AbbVie Inc.). The aim of this study was to investigate the extent to which C31 treatment could also improve the motor axon function in P0 -/-, a CMT model with a much more severe neuropathy. We found that the progressive impairment of motor performance from 1 to 4 months of age in P0 -/- could be acutely reversed by C31 treatment. The effect was associated with an improvement of the amplitude of the plantar CMAP evoked by tibial nerve stimulation. The corresponding motor nerve excitability studies by "threshold tracking" showed changes after C31 consistent with attenuation of a resting membrane depolarization. Our data suggest that the depolarizing motor conduction failure in P0 -/- could be acutely improved by C31. This provides proof-of-concept that treatment with oral subtype-selective NaV 1.8 blockers could be used to improve the motor function in severe forms of demyelinating CMT.